Decoupled Hydroclimate of Central and Southwestern Iran Controlled by the Strength of Southerly‐Westerly Jets During Marine Isotope Stage 3 - M. Soleimani; J. L. Baker; A. Nadimi; Y. Dublyansky; G. Koltai; C. Spötl (Geophysical Research Letters)
Abstract The regional impact of abrupt glacial climate variability remains poorly constrained for arid southwestern Asia, particularly winter dynamics during Marine Isotope Stage 3, due to limited paleoarchives in the Middle East. Here, we present continuous speleothem records of δ18O and δ13C with robust chronologies for southwestern and central Iran, spanning ∼50–30 ka. Stable‐isotope signals in the two stalagmites are generally uncorrelated and do not exhibit a consistent response to Greenland stadials or interstadials; however, both show a positive δ18O excursion that coincides with Heinrich event 4. We explore the potential mechanisms for intermittent coupling of speleothem δ18O across Iran through isotope‐enabled atmospheric modeling outputs, from which we utilize the spatial δ18O gradient as a proxy for wintertime westerly versus southerly jet strength. Our results suggest that during Heinrich event 4 and several Greenland stadials, stronger westerly winds enhanced Mediterranean moisture contributions to both sites and reduced aridity in southern Iran.